Does end-of-life care differ for Anglophones and Francophones? A retrospective cohort study of decedents in Ontario, Canada - Guerin, Ewa; Batista, Ricardo; Hsu, Amy. T.; Gratton, Valérie; Chalifoux, Mathieu; Prud’homme, Denis; Tanuseputro, Peter (Journal of Palliative Medicine, 2018)
Background: Approximately half of decedents in Ontario, Canada, receive some palliative care, but little is known about the influence of language on the nature of these services. Objective: To examine differences between English- and French-speaking residents of Ontario in end-of-life care and outcomes (e.g., health care costs and location of death). Design: A retrospective cohort study using multiple linked databases. Setting/Subjects: A population-based cohort of decedents in Ontario (2010–2013) who were living in long-term care institutions (i.e., nursing homes) or receiving home care before death (N = 25,759). Data from two regions with higher representations of Francophones were examined, with the final distribution by primary language being 75% Anglophone, 18% Francophone, and 7% other languages. Results: Compared with Anglophones, Francophones were more frequent users of long-term care (47.6% vs. 37.1%) and less frequent users of home care (71.3% vs. 76.3%). In adjusted models, the number of days spent in hospital in the last 90 days of life was similar between Anglophones and Francophones, although the odds of dying in hospital were significantly higher among the latter. The mean total health care cost in the last year of life was slightly lower among French ($62,085) compared with English ($63,814) speakers. Conclusions: There are statistically significant differences in end-of-life outcomes between linguistic groups in Ontario, namely more institutionalization in long-term care, less home care use and more deaths in-hospital among Francophones (adjusted). Future research is needed to examine the cause of these differences. Strategies to ensure equitable access to quality end-of-life care are required.

L’influence de l’identité linguistique et de l’âge sur la représentation sociale des services de santé mentale chez les personnes dites dépressives - Lévesque, Maude; Negura, Lilian; Moreau, Nicolas; Laflamme-Lagoke, M. (Minorités linguistiques et société, 2018)
Cet article étudie la représentation sociale des services de santé mentale chez les personnes dites dépressives en contexte francophone minoritaire au Canada. Des entrevues semi-dirigées ont été réalisées auprès de 44 personnes s’identifiant comme francophones et anglophones. Ces dernières proviennent de Moncton, Ottawa, Sudbury et Winnipeg et ont fait l’expérience d’un épisode dépressif. L’analyse lexicographique complétée par l’analyse intégrée de contenu a fait ressortir trois grands schèmes sociocognitifs de la représentation sociale des services, qui agissent sur l’acceptabilité sociale des services de santé mentale chez les personnes francophones vivant en situation minoritaire : 1) la nature impersonnelle des compétences expertes des professionnels de la santé, 2) la facette médicale de l’identité dépressive et 3) la perte perçue du contrôle dans le contexte de soins. L’acceptabilité sociale des services de santé mentale est discutée également en fonction de la configuration de la représentation sociale des services selon l’âge. Mots-clés : minorité linguistique, francophones, santé mentale, services, dépression, représentation sociale

Étude de la situation socioculturelle et linguistique des jeunes franco-ontariennes et franco-ontariens face aux défis d’accès aux services de santé de qualité en français à Timmins - Mafanda-Mahuma, Pierre (Université Laurentienne, 2018)
fs-ref-orig: Mafanda-Mahuma, P. (2018). Étude de la situation socioculturelle et linguistique des jeunes franco-ontariennes et franco-ontariens face aux défis d’accès aux services de santé de qualité en français à Timmins [mémoire de maîtrise, Université Laurentienne]. Zone UL. https://zone.biblio.laurentian.ca/handle/10219/3136 fs-code-orig: Mafanda-Mahuma-2018